"Rafts": A nickname for putative transient nanodomains. (January 2019) - Goñi, Félix M.
Highlights: Membrane rafts have been proposed to be nm-sized, short-lived lipid-protein domains. Methods that would allow visualizing such structures in vivo are only now beginning to emerge. The raft concept maybe an oversimplification for a variety of nanostructures of heterogeneous sizes and functions. It is wrong to equate rafts with detergent-resistant membrane fractions. The term "raft" could be replaced with advantage by "nanodomain". Abstract: The membrane raft hypothesis, proposed in 1997 by Simons and Ikonen, has played a paradoxical role in the history of biomembrane research. While it has generated a large amount of investigations, thus helping to increase our understanding of membranes, the object that gives name to the hypothesis, i.e. the raft itself, has been and still is an object of controversy, in which its very reality is often questioned. In this contribution I review the history of the hypothesis and its reception by membrane biologists, and summarize some of the valuable physico-chemical results that have been obtained while testing the raft hypothesis. To save a useful concept from its many misuses I propose that the expression "(transient) nanodomains" be employed instead of "rafts".